Gestão documental: arquivo setorial do Instituto de Tecnologia (ITEC) da Universidade Federal do Pará - SANTOS, Kale Tatiani Lima dos (2017)
The presente project has as objective, documental management: sectoral archive of Technology Institute from State University of Pará (ITEC/UFPA), doing archival aplication from theory to practice, of the benefits can bring, firstly supporting administration on decisions and then history and citizens. Comprehend, by this, the importance and contribution of documental management, with it’s administatrive rotins, and aplication os archival intruments, according to the proposed model by National Archive and madatory by Ministério da Educação – MEC. The archives organization begins with the elaboration o one diagnosis to identify positive and negative points, raise it’s needs and adequacy to space, people, material, equipment necessary to propose the administration the criation or adequacy of physical space to receive by transfer the documental produced and accumulated by several ITEC’s sectors, for: avaliation, classification, selection, ordnation, packing and archiving for preservation and diffusion of the information. The purpose of organization of these documents and archival instruments aplication on documental management is rationalize the decumentation, saving for posteriority those constitutive documents of ITEC’S administrative and academic acts and facts.